A review of the benefits and uses of garlic (Allium sativum L.) and onion (Allium cepa L.) from Islamic and scientific perspectives - Raihan, Ismil; Nurfatihah, Ali Besar; Ahmad, Khader; Hossain, Md. Sanower (2024)
Background: Garlic (Allium sativum L.) and onion (Allium cepa L.) are herbaceous plants used for their medicinal and culinary properties since ancient times. They are also mentioned in the divine scriptures, such as the Qur'an as al-fum (الفوم) and al-basal (البصل), respectively, which have further popularised their wide utilisation as blessed plants. This study was aimed (1) to analyse scholars' interpretations of garlic and onion in the Qur'an and Hadith, (2) to assess the medicinal benefits of these plants in Islamic medicine, and (3) to explore the relationship between scientific findings and religious beliefs. Methods: The library research method was employed. The literature review was performed using various sources including the Qur’an, Tafsir, Hadith, books, journal articles, and dissertations. Results: The presented review on the benefits and uses of garlic and onion, particularly in medicine from the Islamic perspective, has been scientifically proven, such as for anti-fatigue and chest pain reliever. Garlic and onion possess various phytochemical properties such as antioxidant, antibacterial, and anticancer. These plants have been used to treat several ailments like hypertension, gastritis, and liver disease to name a few. Conclusion: Garlic and onion possess a wide range of benefits and uses, particularly in medicine. Even though the benefits and uses of both plants are not mentioned directly in the Qur'an and Hadith, the analysis of dalil indicates a correlation between the scientific findings of garlic and onion and the revelation that was revealed 1400 years ago before the emergence of science and technology.